Comprehensive study of Handoff Strategy-A Survey (International Journal of Engineering and Computer Science, 2013)
No doubt that due to advancement in wireless technologies and networks, more efficient measures has to be taken to enable the mobile users to be always connected to the best available access network depending on their requirements. For efficient delivery of services to the mobile users, the next-generation wireless networks require new mechanisms of mobility management where the location of every user is proactively determined before the service is delivered. Moreover, for designing an adaptive communication protocol, various existing mobility management schemes are to be seamlessly integrated. Efficient handoff mechanisms are essential for ensuring seamless connectivity and uninterrupted service delivery. This paper gives a brief overview of the handoff related terms and gives an overview of the proposed work. The proposed work focuses on handoff algorithm which selects a good quality access point among the available access points.